Genomic insights into Enterococcus faecalis implicated in endodontic infections: resistance, virulence, and genetic variability: Genomic insights into E. faecalis - Boreak, Nezar; Mowkly, Ahlam Abdu Mohammed; Sharwani, Amnah; Almasoudi, Shroog Ali; Huraysi, Ahmed; Sulily , Ibrahim Ali; Jali, Ghadi Ghamdhan; Basihi, Mohammed Abed; Alfaifi, Osama; Tohari, Elham Ali; Madkhali, Rehaf (Cellular and Molecular Biology, 2025)
Endodontic infections, often involving multispecies bacterial communities, present significant challenges in treatment due to their complex pathogenic mechanisms and resistance to conventional therapies. Enterococcus faecalis is a facultative anaerobic gram-positive bacterium that has been frequently recovered from secondary or persistent endodontic infections. This study investigates the population structure, resistome, mobilome, and virulome of E. faecalis isolated from oral cavity sources, focusing on 22 genomes sequenced from saliva and root canal samples. The genome sequence analysis revealed a diversity of 14 sequence types (STs), highlighting genetic variability within oral E. faecalis populations. Virulence profiling identified 39 genes involved in adherence, biofilm formation, toxin production, stress response, and immune evasion. Antimicrobial resistance (AMR) genes, including lsa(A), efrA, and tetM, were prevalent across all genomes, indicating potential multidrug resistance. Mobile genetic elements (MGEs), such as insertion sequences, transposons, prophages, and plasmids, were also identified, facilitating genetic exchange within and between species. Network analyses identified central virulence genes (e.g., asa1, gelE) and AMR genes (e.g., ANT (6)-Ia, dfrE) crucial for pathogenicity and resistance, highlighting their pivotal roles in E. faecalis infections. This study provides comprehensive insights into the genomic characteristics, AMR genes, virulence factors, and genetic mobile elements associated with E. faecalis isolates from the oral cavity, offering implications for dental health and potential strategies for infection control and treatment.